Pro Active record databases with Ruby and Rails - Marshall, Kevin; Pytel, Chad.; Yurek, Jon.; SpringerLink (Online service) (Berkeley, CA : Springer, 2007)
Provides information on developing database applications in Ruby and Ruby on Rails.
Includes index.
Keywords: Ruby on rails (Electronic resource); Object-oriented programming (Computer science); Ruby (Computer program language); Database management -- Computer programs; Database management; Database design